Why do richer EU countries have a higher public debt ratio than their poorer counterparts? - Grabia, Tomasz (Dlaczego bogatsze kraje UE mają wyższy wskaźnik długu publicznego niż biedniejsze?, 2019)
This article aims to identify the factors differentiating public debt ratios among EU countries with different levels of development. The study period from 2000 to 2018 was adopted. The analysis was extended to the period of 1990-1996, for inflation only. In order to achieve the aim, a time-series analysis and correlation coefficients between selected categories were examined. Based on the above, the analysis indicates that differences in the public debt ratios in EU countries stemmed also from reasons that do not result from Keynesian and non- -Keynesian effects, such as: (i) varying economic growth rates (according to the theory of real convergence); (ii) varying inflation rates; (iii) different conditions relating to the stabilization of debt ratios in the context of primary balance volumes
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 12, s. 35-48